Shapeable Maximum-Power Point-Tracking Algorithm To Improve The Stability Of The Output Behavior Of A Thermoelectric-Solar Hybrid Energy-Harvesting System - Md Yusop, Azdiana; Mohamed, Ramizi; Ayob, Afida; Mohamed, Azah (Taylor & Francis, 2017)
This study presents the development of a novel maximum-power point-tracking (MPPT)method based on an input shaping scheme controller.The proposed method that changes the initial input response into a shapeable MPPT algorithm is designed based on an exponential input function.This type of input function is selected because of its capability to stabilize the system at the end of the simulation time and remain at the same condition at the final response time.A comparison of the system with the proposed method and the system with traditional perturb and observe (PnO)method is also provided.Results show that the system with the proposed method produces higher output power than the system with PnO method;the difference is approximately 15.45%.Results reveal that the exponential function input shaper allows the overall output system to exhibit satisfactory behavior and can efficiently track the maximum output power.